Age hardening and ex-situ EBSD analysis of high vacuum die casting Mg–4Al-4RE-0.3Mn alloy - Yongfeng Li; Ang Zhang; Chuangming Li; Hecong Xie; Hengrui Hu; Yuyang Gao; Yan Yang; Jiangfeng Song; Zhihua Dong; Bin Jiang (Journal of Materials Research and Technology, 2025)
The microstructure and properties of high vacuum die casting Mg–4Al-4RE-0.3Mn (HVDC-AE44) alloy before and after aging are investigated, and the evolution of twinning and texture during axial compression and tensile deformations at 150 °C after aging is analyzed using ex-situ EBSD. The results indicate that Al4Mn phase precipitates in the HVDC-AE44 after aging, and the crystallographic orientation relationship between Al4Mn and Al11RE3 is (2 2‾ 2)Al4Mn//(1 1‾ 1)Al11RE3. Compared with die-cast alloy, the precipitation of nanoscale mid-temperature stable Al4Mn phase effectively enhances the properties of the alloy, resulting in 30.9 MPa and 10.8 MPa increase in UTS and 22.9 MPa and 20.1 MPa increase in YS of the aged HVDC-AE44 alloy during tensile deformation at room temperature and 150 °C, respectively. During compression deformation at 150 °C, the compression strength increases by 3.4 MPa, 7.9 MPa, and 4.6 MPa when the compression strains are 5 %, 15 %, and 20 %, respectively. When compression deformation at 150 °C, the SF of {10 1‾ 1} compressive twins and {101‾ 2}-{101‾ 2} double twins is higher than that of {101‾ 2} tensile twins. As the compression strain increases from 5 % to 20 %, the grain fragmentation and the formation of substructures cause the proportion of HAGBs and {101‾ 2} change from 54 % to 23 % and 27.0 % to 3.7 %, respectively. When tensile deformation at 150 °C, large strain and grain rotation at position 1 result in significantly increase texture strength at position 1, and {10 1‾ 2} are formed in the coarse grains to coordinate deformation.